Persian manuscripts on cannon making, different types of ordnances (cannons, howitzers and mortars), rockets and fireworks - Khorasani, M.M. (Історія давньої зброї. Дослідження 2014, 2014)
The goal of this article is to give a short overview of some Persian manuscripts on casting bronze cannons, the usage of rockets and different types of ordnance such as cannons, mortars and howitzers. Additionally, some manuscripts on shooting rockets that did not require a bombarding frame will also be discussed in the present article. A manuscript on making and shooting fireworks will also be introduced in the manuscript.